2014
DOI: 10.1155/2014/598986
|View full text |Cite
|
Sign up to set email alerts
|

Importance of pH Homeostasis in Metabolic Health and Diseases: Crucial Role of Membrane Proton Transport

Abstract: Protons dissociated from organic acids in cells are partly buffered. If not, they are transported to the extracellular fluid through the plasma membrane and buffered in circulation or excreted in urine and expiration gas. Several transporters including monocarboxylate transporters and Na+/H+ exchanger play an important role in uptake and output of protons across plasma membranes in cells of metabolic tissues including skeletal muscle and the liver. They also contribute to maintenance of the physiological pH of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 88 publications
1
118
0
1
Order By: Relevance
“…It is worth mentioning that the pH of the human body lies in a tight range between 7.35 and 7.45, and any minor alterations from this range can lead to several disorders. For example, arthritis as one of the most disabling diseases in developed countries is related to pH imbalance and accumulation of acid deposits in the joints and wrists . The allergic reactions are also expected by using an acidic or basic product.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the pH of the human body lies in a tight range between 7.35 and 7.45, and any minor alterations from this range can lead to several disorders. For example, arthritis as one of the most disabling diseases in developed countries is related to pH imbalance and accumulation of acid deposits in the joints and wrists . The allergic reactions are also expected by using an acidic or basic product.…”
Section: Resultsmentioning
confidence: 99%
“…An ex vivo study by Yamauchi et al (24) reported that insulin-mediated 2-deoxy-D-glucose uptake by rat soleus muscle is inhibited by a reduction in the pH of the medium from 7.4 to 6.8. Furthermore, Aoi et al (25) have reported that a propolis-contained diet improved, by increasing, the pH of ascites and metabolic tissues compared to the normal diet and improved glucose metabolism in Otsuka Long-Evans Tokushima Fatty rats, whose pH in various tissues was lower compared to normal rats (25)(26)(27). Therefore, propolis may improve insulin sensitivity by an increase of extracellular pH.…”
Section: Placebo (N=39)mentioning
confidence: 99%
“…While the pH of human body fluid is well-regulated by homeostasis to be maintained at pH 7.4, the pH of the tumor microenvironment is slightly acidic (pH 5.5 to 7.0) due to glycolytic metabolism, hypoxia, and deficient blood perfusion [41, 42]. Although Ho was shown to bind to GONs quantitatively at pH >4 in the sorption study, holmium was observed to be slowly released from the GONs in the leaching study when the pH of the medium was 5.5 due to a change in equilibrium resulting from the larger volume of dialysate in the leaching study.…”
Section: Discussionmentioning
confidence: 99%